THE MANUFACTURE OF BIODEGRADABLE FILM FROM CEMPEDAK SEED STARCH AND CARBOXY METHYL CELLULOSE WITH THE ADDITION OF GLYCEROL - Elean, Samuel; Saleh, Chairul; Hindryawati, Noor (JURNAL ATOMIK, 2018)
This research about the manufacture of biodegradable film from cempedak (Artocapus champeden sp.) seed starch and CMC (Carboxy Methyl Cellulose) as well as with the addition of glycerol as a plasticizer has been studied. The purpose of this research are to knowing the concentration of glycerol which have the best of tensile strength, percent elongation, water uptake and biodegradability and knowing the characteristic of biodegradable film produced. In this research the ratio of starch: CMC used is 7:3 while the concentration glycerol is added 10%, 20%, 30% and 40% from the weight of starch. The result of the best concentration of glycerol is glycerol 10%. Glycerol 10% produce a film with 19.62 N/mm2 of tensile strength, 4.98% of percent elongation, 54.33% of water uptake and 39.96% of degradation in 2 days with degradability 24.9 mg/day. Biodegradable film characterized by using FT-IR, analysis result of functional groups showing there are alcohol (O-H) and eter (C-O) groups which indicates that the film is biodegradable.